Benefits and limitations of the informal economy in promoting sustainable and inclusive local economic development: A Stellenbosch case study - Tshofuti, Lelethu (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.